International financial liberalization and industry growth - Jonas Vlachos; Daniel Waldenström (Stockholm School of Economics, The Economic Research Institute (EFI), 2002)
The growth effects of international financial liberalization and integration are investigated using the methodology and data developed by Rajan and Zingales (1998). The main result is that industries highly dependent on external financing do not experience higher growth in value added in countries with liberalized financial markets. Liberalization does, however, increase the growth rates of both production and firm creation among externally dependent industries - given that countries have reached a relatively high level of financial development. These results are consistent both with increased competition and increased outsourcing. Some preliminary evidence point towards the latter explanation.
Keywords: F30; G10; O40; 330; Financial liberalization; Financial integration; Economic growth; Wirtschaftswachstum; Kapitalmarktliberalisierung; Marktintegration; Internationaler Finanzmarkt; Schätzung